Римські бронзові черпаки у варварів Північного Причорномор’я - Симоненко, О.В. (Археологія, 2023)
У статті розглянуто всі відомі знахідки римських бронзових черпаків у сарматських та пізньоскіфських пам’ятках на територіях України,
Молдови, Румунії. Проведено типологічне визначення знахідок за відомими класифікаційними
схемами, обґрунтовано датування та здійснено
їх міжкультурний порівняльний аналіз. The paper examines all known finds of Roman bronze casseroles from the Sarmatian and Late Scythian burials in the territories
of Ukraine, Moldova, and Romania. The items were classified according to relevant typological schemes, the dating of the finds
was substantiated and a cross-cultural comparative analysis was carried out.
Bronze casseroles, which were part of the equipment of a Roman legionary, are probably the most numerous type of Roman
metal vessels found in the Sarmatian and Late Scythian burials. The typology and chronology of Roman bronze casseroles is well
developed, and they are a reliable chronological marker. Roman bronze casseroles from the Sarmatian and Late Scythian burials
of modern Ukraine, Moldova, and Romania have been studied in several works, but a comparative analysis of these vessels among
the Sarmatians and Late Scythians of the Northern Pontic region has not yet been conducted and is one of the tasks of this work.
Ten bronze casseroles have been discovered in the Sarmatian graves in modern Ukraine, Moldova and Romania and seven
ones in the Late Scythian burials in the Crimea.
The Sarmatian assemblages with Roman casseroles of Eggers types 137—144 in the Northern Pontic region are dated from
the second half of the 1st to the mid-2nd centuries AD. It should be noted that the majority of similar vessels from Asian Sarmatia
were also found in the graves dated mainly to the second half of the 1st — the first third of the 2nd centuries AD. There is a
version that such casseroles got to the Sarmatians after the Bosporus-Roman war of 45—49 AD. A somewhat different picture is
observed among the Late Scythians. All assemblages with Roman casseroles are dated since the mid-1st century AD (Ust-Alma,
grave no. 720, Eggers type 133) until the last quarter of the same century (the rest of the assemblages of Ust-Alma and Belbek IV
burial grounds).
Sarmatian graves with casseroles have been accompanied by various and often expensive grave goods. The burials of the
Late Scythian necropoli with bronze vessels also belonged to the wealthy members of the community.
The assortment of Sarmatian and Late Scythian imported casseroles is somewhat different — the Sarmatians had no early
casseroles of Eggers types 133—136, and the Late Scythians had no Gödåker type casseroles (Eggers type 144). There are no
casseroles in the Late Scythian burials of the Lower Dnipro region, all finds are concentrated in the Crimea.